Penerapan Model Problem Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMA Kelas X - Suryani Sirait; Lisa Aryanti Pohan; Susylawati Sinambela (Journal on Education, 2024)
This type of research is classroom action research which aims to determine the increase in students' mathematical problem solving abilities on exponential root form material through the application of the Problem Based Learning (PBL) learning model. This research was carried out in class Data collection techniques were carried out by observation, interviews and tests. The research was carried out in 2 cycles with data acquisition carried out by direct observation (peer assessment) by researchers and self-assessment by students during teaching and learning activities. Based on the data obtained, then carry out analysis using descriptive statistical analysis, namely that the parameter for the success of the research is the increase in the average student collaboration skills in each cycle. In accordance with what the researchers have done, the results of the analysis showed that the percentage increase in the average score of students' mathematical problem solving skills tests on root form material was 72.8% from cycle 1 to cycle 11 as well as a count of observations regarding the increase in the completeness of student learning outcomes from cycle 1 to cycle 2 is 55.17%.